Synthesis and characterization of xMgO-1.5Al2O3-5SiO2 (x = 2.6-3.0) system using mainly talc and kaolin through the glass route - Banjuraizah, Johar (Elsevier B.V., 2011)
Link to publisher's homepage at http://www.elsevier.com